Pasar Nagari Ujung Gading Kabupaten Pasaman Barat Sebagai Sentral Perekonomian Masyarakat 2002-2021 - Reni Widhaswara; Etmi Hardi (Jurusan Sejarah FIS UNP, 2022)
This research is a historical study that discusses the development of the Nagari Market UjungGading, West Pasaman Regency as the center of the community's economy 2002-2021. Thepurposei of this study is to explain the development of the Ujung Gading Nagari Market when itwas managed by the Ujung Gading Kenagarian, and to explain the role of the Ujung GadingNagari Market as the center of the community's economy. This study uses the historical methodthrough four stages, namely: heuristics, source criticism, interpretation and historiography. Theresults of the study indicate that the Nagari Ujung Gading Market has increased optimallystarting from buildings, infrastructure facilities, management, and economic activities, as well asthe role of the market as the center of the economy of the people of Nagari Ujung Gading and itssurroundings.